Self-psychological and zakat institution factors: it is reliable to influence intention to pay zakat among muslim in Kuala Terengganu / Nurul Fatehah Mohd Azam - Mohd Azam, Nurul Fatehah (Faculty of Business and Management, 2019)
Paying zakat has been practice long time ago in Prophet Muhammad SAW era. Zakat is one of pillars in Islam. Now days, there åre lower collection rate of the zakat funds, significantly it will give a bad perception toward the Islam itself because it will increase the percentage of poor people among the Muslim community. Therefore, it is very important to make sure a Muslim people have a high level of intention to pay zakat. Hence, in this study, the main objective is to determine the levels of intention to pay zakat among Muslim. Besides that, this study also aims to examine the effects of five selected cause factors (i.e. Role Identity, Self-Religiosity, Subjective Norm, Satisfaction and Corporate Reputation) toward the intention to pay zakat among Muslim. All these six variables were treated as a primary data, since all these variables were measures directly from the targeted respondents. In this study, around 200 Muslim's resident at Kuala Terengganu that passing the criteria about able to pay zakat will be targeted sample. The study was conducted at Kuala Terengganu, where focusing on Muslim residents and 200 respondents were participated in this study. The findings indicated that, all these five selected independent variables such as role identity, self-religiosity, subjective norm, satisfaction, and corporate reputation will give a positively significant influence toward the intention to pay zakat among Muslim.